Evaluating Nanofiltration Effect on Wine 87Sr/86Sr Isotopic Ratio and the Robustness of this Geographical Fingerprint - Moreira, Cíntia; de Pinho, Maria; Curvelo-Garcia, António; de Sousa, Bruno; Ricardo-da-Silva, Jorge; Catarino, Sofia (South African Journal of Enology and Viticulture, 2017)
When aiming to use the strontium isotopic ratio 87Sr/86Sr for the traceability and authentication of wine, it is crucial to understand the impacts of anthropogenic factors and technological processes on this parameter. A study was developed to evaluate the effect of nanofiltration (NF), a membrane process with several applications in oenology, on the isotopic ratio 87Sr/86Sr of wine, testing its robustness as geographical tracer. NF assays, for dealcoholisation, were carried out at laboratory scale with model solutions and white and red wines from Portuguese DO. High rejections to strontium (97%) and tartaric acid (> 70%) and low rejection to ethanol (< 10%) at 15 bar were observed in model solutions. Wines and NF-processed wines (17 bar; 2.1 L/min) were evaluated for physicochemical composition (including phenolic composition, chromatic characteristics and polysaccharides), multi-elemental composition and 87Sr/86Sr ratio by Q-ICPMS. The preferential membrane permeation of ethanol was associated with a slight increase in the quality parameters of the wine (anthocyanins and polysaccharides). High rejections to mineral elements, including heavy metals, were observed. Rejection to Sr was mostly higher than 95%. No significant differences in the 87Sr/86Sr of wines and corresponding permeate fractions were observed, suggesting that NF does not preclude the use of this parameter for wine traceability purposes.